New Penal Paradigm: Proportional and Restorative Strategies to Manage Overcrowding at Class I Tanjung Gusta Detention Center - Agung Adipa Dewantara Siregar; MHD. Teguh Syuhada Lubis (Yayasan Abdurrauf Cendekia Nusantara, 2026)
This study highlights overcrowding in the Class I State Prison Tanjung Gusta Medan as a consequence of the dominance of prison sentences and excessive detention practices in the Indonesian criminal justice system. This problem is structural because it is rooted in the orientation of repressive penal policies and the application of alternative sanctions has not been optimal. This research uses a normative juridical method with a statute approach and is supported by literature studies on primary, secondary, and tertiary legal materials. The results of the study show that Law Number 1 of 2023 concerning the Criminal Code marks a paradigm shift from a retributive approach to a corrective, rehabilitative, and restorative approach, with imprisonment as the ultimate remedium. The implementation of alternative criminal justices, such as social work crimes, supervision crimes, diversion, restorative justice, and the optimization of integration programs (assimilation and parole), has been proven to have the potential to suppress the influx of new prisoners, increase the effectiveness of coaching, and maintain the proportionality of punishment. Preventing overcrowding requires consistency in the application of the new paradigm so that the penal system runs rationally, risk-based, and fair.